IDENTIFIKASI POTENSI PARIWISATA BERBASIS ANALISIS SWOT DI PULAU MAKALEHI KABUPATEN SIAU TAGULANDANG BIARO (SITARO) PROVINSI SULAWESI UTARA - Chrisye M Katulung; Bet El S. Lagarense; Merry Adrah (Jurnal Ilmu Pariwisata, 2022)
Tourism is an activity of leisure to regain the freshness of the soul and mind, more that it is an industry that promises great benefits for anyone who wants to participate and work in it. This research was conducted in Lembean village Kauditan Disctrict, North Minahasa Regency North Sulawesi, Indonesia. There is a natural tourist attraction that has not been touched and developed yet called Seper Lake. This research was conducted with the aim of identifying what are tourism potential that Seper Lake has. The data anlysis technique used in this study is a descriptive qualitative research method using SWOT anlysis. The method of data collection conducted by researcher are interviews to several parties who are able to provide accurate information. Direct bservation was carried out in Seper Lake and also documentation and library studies. The results showed that Seper Lake has high tourism potential power if developed and managed properly, such as the atmosphere around the lake that is still natural and cool air, as well as the presence of lakes located in villages with richness in culture.